2011
DOI: 10.1016/j.jadohealth.2010.07.019
|View full text |Cite
|
Sign up to set email alerts
|

How Do Adolescents View Health? Implications for State Health Policy

Abstract: Objectives Policy-makers rarely consult adolescents during health policy development. However, adolescent perspectives on health can inform public health policies and programs. As part of the development of an Indiana state plan for adolescent health, we used qualitative methods to describe adolescents' “emic” views of health, and discuss implications for a state health policy for youth. Patients and Methods We conducted 8 adolescent focus groups in geographically and culturally diverse regions of Indiana. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 26 publications
3
49
0
1
Order By: Relevance
“…In these studies the broader views became more apparent following further discussion in focus groups (Ott et al, 2011) and interviews (Natapoff, 1978) or through the use of an open question survey, similar to the one used in this study (Ward and Wang, 1997;Wang, 2004). Notably, common broader views across the studies, including this study, included stress and fatigue (Ott et al, 2011;Ward and Wang, 1997), dealing with problems/emotions (Ward and Wang, 1997;Adler and Wahl, 1998) and non-specific mental health (Wang, 2004) (getting enough sleep/rest was classed as related to both physical and mental health in this study).…”
Section: Baseline Views About Healthmentioning
confidence: 96%
See 1 more Smart Citation
“…In these studies the broader views became more apparent following further discussion in focus groups (Ott et al, 2011) and interviews (Natapoff, 1978) or through the use of an open question survey, similar to the one used in this study (Ward and Wang, 1997;Wang, 2004). Notably, common broader views across the studies, including this study, included stress and fatigue (Ott et al, 2011;Ward and Wang, 1997), dealing with problems/emotions (Ward and Wang, 1997;Adler and Wahl, 1998) and non-specific mental health (Wang, 2004) (getting enough sleep/rest was classed as related to both physical and mental health in this study).…”
Section: Baseline Views About Healthmentioning
confidence: 96%
“…Additionally, little is known about how young people perceive mental health and health in general, in regards to themselves and others, but it has been suggested that their perceptions of mental health differ from those expected by adults and policy makers (Naylor et al, 2009). A limited amount of research has shown views of health to be broader than just physical health for United States (US) (Ott et al, 2011;Natapoff, 1978), Australian (Ward and Wang, 1997) and Chinese (Wang, 2004) young people, but assessment of unprompted beliefs about health remains relatively understudied.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 When pediatricians discuss sensitive topics with adolescents, instead of reporting discomfort, adolescents reported that the pediatrician understood their problems, eased their worries, and allowed them to make treatment decisions. 27 Best-practices guidelines require that the sexual history be taken with the adolescent alone.…”
Section: Taking a Sexual Historymentioning
confidence: 99%
“…Research suggests that adolescents are capable of understanding this type of complex message and, in fact, may disregard messages that they consider judgmental or overly simplified or that eliminate key health information. 25,26 More detailed information on motivational interviewing with adolescents can be found in recent publications. 35,38 Abstinence Counseling in the Office Setting Table 3).…”
Section: Counseling Using Motivational Interviewingmentioning
confidence: 99%
“…1 Adolescents consider pediatricians and other health care providers a highly trusted source of sexual health information. 4,5 Pediatricians' long-term relationships with adolescents and families allow them to ask about sensitive topics, such as sexuality and relationships, and to promote healthy sexual decision-making, including abstinence and contraceptive use for teenagers who are sexually active. Additionally, medical indications for hormonal contraception, such as dysmenorrhea, heavy menstrual bleeding or other abnormal uterine bleeding, acne, and polycystic ovary syndrome, are often uncovered during adolescent visits.…”
Section: Introductionmentioning
confidence: 99%